Produção de celulases e xilanases por Penicillium echinulatum em biorreator com agitação mecânica - Reis, Laísa dos (My University, 2014)
Cellulases and xylanases are enzymes that hydrolyze cellulose and xylan respectively, which are found in lignocellulosic residues. Although the applicability of these enzymes in the ethanol production has been the subject of several studies, an economically viable technology for the production of biofuel from lignocellulosic biomass is currently not available. Strains of Penicillium echinulatum are among the microorganisms that have high titers of these enzymes. However, data related to physiology and enzyme production in bioreactor for such strains are still missing. A cellulolytic mutant strain of P. echinulatum S1M29 and a culture medium composed of cellulose, sucrose, salt solution, Tween 80, wheat bran and soybean meal were used in this study. The effect of different temperatures and pHs during the enzymes production was evaluated. The effect of cellulose concentration in the enzymatic activity was evaluated in batch cultivation (BC) and fed-batch cultivation (FBC). It was found that the appropriate temperature for the production of cellulases and xylanases is 28°C, while the higher enzyme production occurred at pH 6.0. The high cellulose concentration in BC provided the greatest activities for endoglicanases, but the same result was not obtained for xylanases. For Filter Paper Activity (FPA), proportional increases in activity were obtained only with concentrations up to 3% of cellulose in BC, which is also linked to the highest activities for -glucosidases. FBC increased the activities of FPA, endoglucanases and xylanases, but it did not increase the -glucosidases activities. Such results contribute towards the optimization of enzyme production using P. echinulatum and the development of economically viable technologies for the production of ethanol from lignocellulosic materials.
As celulases e as xilanases são enzimas que hidrolisam a celulose e a xilana, respectivamente, contidas nos resíduos lignocelulósicos. A possibilidade de aplicar estas enzimas na produção de etanol vem sendo objeto de diversos estudos. No entanto, ainda não há uma tecnologia economicamente viável para a produção deste biocombustível a partir da biomassa lignocelulósica. Entre os microrganismos que apresentam altos títulos para estas enzimas, incluem-se linhagens de Penicillium echinulatum; porém, ainda faltam dados de sua fisiologia e estudos da produção de enzimas em biorreator. Neste trabalho, empregou-se a linhagem mutante celulolítica desreprimida S1M29 de P. echinulatum e o meio de cultivo foi composto por celulose, sacarose, solução de sais, Tween 80, farelo trigo e farelo de soja. Avaliou-se o efeito de diferentes temperaturas e pHs na produção das enzimas. O efeito da concentração da celulose sobre as atividades enzimáticas foi avaliada em regime descontínuo (RD) e regime descontínuo alimentado (RDA). Verificou-se que a temperatura mais apropriada para a produção de celulases e xilanases é de 28ºC e dentre os valores de pHs avaliados, o pH 6,0 apresentou a maior produção das enzimas. O aumento da concentração da celulose no RD proporcionou maiores atividades para endoglicanases, porém o mesmo não foi obtido para xilanases. Para FPA (Filter Paper Activity), aumentos proporcionais nas atividades foram obtidos somente com concentrações de até 3% de celulose em RD, condição que também proporcionou as maiores atividades de - glicosidases. O RDA incrementou as atividades de FPA, endoglicanases e xilanases, mas não de -glicosidases. Estes resultados contribuem para a otimização de processos e para a produção econômica de enzimas por P. echinulatum, visando o desenvolvimento de tecnologias economicamente viáveis para produção de etanol a partir de materiais lignocelulósicos.
Keywords: Enzimas; Celulase; Xilanases; Penicillium echinulatum; Cellulase; Xylanases; Bioreactors